Work stressors and vicarious trauma among South African Police Service members. Issue 3 (4th May 2022) - Gumani, Masefako Andronica
Abstract : This study explored vicarious stress experiences of South African Police Service members from a rural district serving victims of trauma. Informants were 19 police members (female = 26.3%; constables = 21%; age range = 27 to 55). The police members completed open-ended interviews about their experiences when engaging with victims of trauma. Following interpretative phenomenological analysis, findings indicated that the police members experienced vicarious types of stress due to their operational work, personal situations, and cultural prescriptions. Operational work vicarious stressors included perceptual stressors and police-victim interpersonal closeness. Personal situations vicarious stressors were due to cognitive overload resulting from vocation-life association and personal trauma history. Cultural-prescriptive stressors of societal cultural beliefs were also associated with vicarious trauma. These findings suggest a need for culturally appropriate mental health services and identifying personal and organisational strategies to manage vicarious traumatisation in the police services.